Analisis pendapatan dan konsumsi petani karet di Desa Sungai Ulak Kecamatan Nalo Tantan Kabupaten Merangin - Bayu Prasetyo; Syaparuddin Syaparuddin; Selamet Rahmadi (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
This study aims: 1). To measure and analyze the income of rubber farmers in Sungai Ulak Village, Nalo Tantan District, Merangin Regency, 2). To measure and analyze the consumption issued by rubber farmers in Sungai Ulak Village, Nalo Tantan District, Merangin Regency and 3). the effect of income on consumption issued by rubber farmers in Sungai Ulak Village, Nalo Tantan District, Merangin Regency. The analytical method used in this research is quantitative descriptive analysis and simple linear regression analysis.Based on the results of the study concluded. The income of rubber farmers has a positive and significant effect on α = 5% one-way test on the total consumption of rubber planters in Sungai Ulak Village, Nalo Tantan District, Merangin Regency with a regression coefficient value of 0.836425.